A maior rede de estudos do Brasil

Grátis
6 pág.
Derivada - Regra da cadeia / Derivação Logarítmica

Pré-visualização | Página 2 de 2

ysen(x) = xcos(y);
e) y = (x
2+1)10(x−1)5
(3x4+2x)8 ;
f) y =
5
√
sen(x)(x3+2)10
x8(1−x5) .
Respostas: a) y′ =
(
x
x+1 + ln|x + 1|
)
(x + 1)x, b) y′ = (−xtg(x) + ln|cos(x)|)(cos(x))x, c) y′ = 1x(ln|y|+1) ,
d) y′ =
cos(y)
x −cos(x)ln|y|
sen(x)
y +sen(y)ln|x|
, e) y′ =
(
20x
x2+1 +
5
x−1 − 8(12x
3+2
3x4+2x
)
(x2+1)10(x−1)5
(3x4+2x)8 ,
f) y′ =
(
cos(x)
5sen(x) +
30x2
x3+2 − 8x + 51−x
) 5√sen(x)(x3+2)10
x8(1−x5)
5